The effect of ambient temperature on gross-efficiency in cycling - Hettinga, F. J.; Koning, J. J.; de Vrijer, A.; Wüst, R. C. I.; Daanen, H. A. M.; Foster, C. (European Journal of Applied Physiology, 2007)
Time-trial performance deteriorates in the heat. This might potentially be the result of a temperature-induced decrease in gross-efficiency (GE). The effect of high ambient temperature on GE during cycling will be studied, with the intent of determining if a heat-induced change in GE could account for the performance decrements in time trial exercise found in literature. Ten well-trained male cyclists performed 20-min cycle ergometer exercise at 60% PV\textO\text2max PVO2max (power output at which VO2max was attained) in a thermo-neutral climate (N) of 15.6 ± 0.3°C, 20.0 ± 10.3% RH and a hot climate (H) of 35.5 ± 0.5°C, 15.5 ± 3.2% RH. GE was calculated based on VO2 and RER. Skin temperature (T sk), rectal temperature (T re) and muscle temperature (T m) (only in H) were measured. GE was 0.9% lower in H compared to N (19.6 ± 1.1% vs. 20.5 ± 1.4%) (P < 0.05). T sk (33.4 ± 0.6°C vs. 27.7 ± 0.7°C) and T re (37.4 ± 0.6°C vs. 37.0 ± 0.6°C) were significantly higher in H. T m was 38.7 ± 1.1°C in H. GE was lower in heat. T m was not high enough to make mitochondrial leakage a likely explanation for the observed reduced GE. Neither was the increased T re. Increased skin blood flow might have had a stealing effect on muscular blood flow, and thus impacted GE. Cycling model simulations showed, that the decrease in GE could account for half of the performance decrement. GE decreased in heat to a degree that could explain at least part of the well-established performance decrements in the heat.